The patient co‐payment and opportunity costs of accessing healthcare for Indigenous Australians with cancer: A whole of population data linkage study. Issue 6 (16th July 2019) - Callander, Emily; Bates, Nicole; Lindsay, Daniel; Larkins, Sarah; Preston, Robyn; Topp, Stephanie M.; Cunningham, Joan; Garvey, Gail
Abstract: Aim: To quantify the direct out‐of‐pocket patient co‐payments and time opportunity costs (length of hospital stay) incurred by Indigenous and non‐Indigenous persons diagnosed with cancer during the first year postdiagnosis. Methods: CancerCostMod was used, which is a model of cancer costs based upon a whole‐of‐population data linkage. The base population was a census of all persons diagnosed with cancer in Queensland, Australia between 1 July 2011 and 30 June 2012 (n = 25, 553). Individual records were linked to corresponding Queensland Health Admitted Patient Data Collection, Emergency Data Information System, Medicare Benefits Schedule, and Pharmaceutical Benefits Scheme records between 1 July 2011 and 30 June 2015. Queensland data were weighted to be representative of the Australian population (approximately 123, 900 Australians, 1.7% Indigenous Australians). Results: After adjusting for age, sex, rurality, area‐based deprivation, and cancer group, Indigenous Australians accrued significantly less in postdiagnosis patient co‐payments at 0–6 months (61% less) and 7–12 months (63% less). Indigenous Australians also had significantly fewer postdiagnosis hospitalizations at 0–6 months (21% fewer) and 7–12 months (27% fewer). Conclusion: There is growing concern regarding the financial burden of cancer to the patient. The time spent away from family and their community may also have an important time opportunity cost, which may affect a person's decision to undertake or continue treatment. This is the first study in Australia to identify the financial cost of co‐payments for Indigenous people with cancer, as well as the number and length of hospitalizations as drivers of time opportunity costs.